2020
DOI: 10.1186/s41935-020-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

Medico-legal evaluation and trend of the different patterns of maxillofacial fractures concomitant with closed head injury in Upper Egypt: retrospective study

Abstract: Background: Maxillofacial fractures are of great medico-legal implications because they are of common occurrence with other injuries, predominantly head injuries that might involve serious esthetic and functional problems, and so clinically described as consequential injuries. The aims were to assess the medico-legal aspects of maxillofacial fractured cases concomitant with closed head injury over a 6-year period (2011-2016) in the Trauma Unit of Assiut University Hospitals, Egypt, and to evaluate the demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…reported that males represent 88% of cases (12). Road traffic accidents were found to be the most frequent cause of fractures accounting for 62.5% of the cases, followed by falls 20.0% then violent assaults 17.5%, which was in agreement with El Shehaby et al, and Chen et al, (12) (13). This may be attributed to the fact that the females drive vehicles less frequently and more carefully than males.…”
Section: Discussionsupporting
confidence: 79%
“…reported that males represent 88% of cases (12). Road traffic accidents were found to be the most frequent cause of fractures accounting for 62.5% of the cases, followed by falls 20.0% then violent assaults 17.5%, which was in agreement with El Shehaby et al, and Chen et al, (12) (13). This may be attributed to the fact that the females drive vehicles less frequently and more carefully than males.…”
Section: Discussionsupporting
confidence: 79%
“…However, this result is higher than the one found by Lebeau, et al, in France in 2006 who reported a gender ratio of 2. This difference can be explained by the fact that in the West, women are much more active and involved in economic, cultural and social activities; thus, they are equally exposed to RTAs, sports accidents and assaults [13].…”
Section: Discussionmentioning
confidence: 99%